2006
DOI: 10.1111/j.1464-410x.2006.06271.x
|View full text |Cite
|
Sign up to set email alerts
|

Radical prostatectomy in patients infected with human immunodeficiency virus

Abstract: OBJECTIVE To present the complications and early outcomes in a small series of men infected with human immunodeficiency virus (HIV) and treated with radical prostatectomy (RP) for prostate cancer, and to review reports on surgery in HIV‐positive patients. PATIENTS AND METHODS During 2002–2005, seven men infected with HIV underwent RP at our institution. For the five patients whose HIV status was known before surgery, we retrospectively examined preoperative variables, including HIV‐specific data (clinical cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…Some authors have suggested that PCa may be more aggressive in patients with HIV; although this study has a limited number of HIV-positive patients with high CD4 counts and low viral loads, it does not support these assertions. 25 The findings of Huang et al 21 were similar to ours (although with a smaller series, different surgical approach and longer follow-up): negative surgical margins in five patients with known HIV who underwent open radical retropubic prostatectomy. No patients had biochemical recurrence after a median follow-up of 26 months.…”
Section: Ralp In Men With Hiv Jl Silberstein Et Alsupporting
confidence: 76%
See 1 more Smart Citation
“…Some authors have suggested that PCa may be more aggressive in patients with HIV; although this study has a limited number of HIV-positive patients with high CD4 counts and low viral loads, it does not support these assertions. 25 The findings of Huang et al 21 were similar to ours (although with a smaller series, different surgical approach and longer follow-up): negative surgical margins in five patients with known HIV who underwent open radical retropubic prostatectomy. No patients had biochemical recurrence after a median follow-up of 26 months.…”
Section: Ralp In Men With Hiv Jl Silberstein Et Alsupporting
confidence: 76%
“…[19][20] Radical retropubic prostatectomy, 21 laparoscopic radical prostatectomy, 22 cryosurgery, 22 external beam radiation therapy, 23 brachytherapy 24 and active surveillance 22 have been reported for HIVpositive men with localized PCa and found to be generally safe and efficacious in the short term. 17 The oncological risk posed by PCa in the HIV-positive cohort did not differ significantly from the non-HIVpositive cohort, based on a variety of prognostic data including PSA value, clinical tumor stage, biopsy Gleason sum, D'Amico risk stratification and pathological tumor grade or stage.…”
Section: Ralp In Men With Hiv Jl Silberstein Et Almentioning
confidence: 99%
“…HIV-positive men with biopsy-proven localized PCa have undergone a variety of interventions; Huang et al 13 have published the largest series of radical prostatectomies in HIV-positive individuals to our knowledge. They retrospectively reviewed all patients who had undergone prostatectomy at Memorial SloanKettering Cancer Center over a two-and-a-half-year period and identified five men who had HIV before prostatectomy.…”
Section: Radical Prostatectomymentioning
confidence: 99%
“…In early decades, surgeons were hesitant to perform elective and emergency procedures to this group of patients due to high complication rates (3,6). The development of HAART in the mid-1990s, presented as the cornerstone for the decrease of the morbidity and mortality rates associated with HIV infection in these patients.…”
Section: Discussionmentioning
confidence: 99%